Declaration of Margarita UNASUR. Building the energy integration of the South - Naciones Suramericanas, Unión de (2007)
The heads of State and Government of Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Guyana, Paraguay, Peru, Uruguay, Suriname and Venezuela, gathered in the city of Porlamar, Nueva Esparta State of the Bolivarian Republic of Venezuela on 17 April 2007, in accordance with the conclusions and recommendations presented by the Energy Ministers during its II Meeting.